2016
DOI: 10.1038/srep39042
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the transition from primary to peritectic phase growth during solidification of undercooled Ni-Zr alloy levitated by electromagnetic field

Abstract: The Ni83.25Zr16.75 peritectic alloy was undercooled by electromagnetic levitation method up to 198 K. The measured dendritic growth velocity shows a steep acceleration at a critical undercooling of ΔTcrit = 124 K, which provides an evidence of the transition of the primary growth mode from Ni7Zr2 phase to peritectic phase Ni5Zr. This is ascertained by combining the temperature-time profile and the evolution of the solidified microstructures. Below the critical undercooling, the solidified microstructure is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Deep undercooling may affect the solidification pathway of alloy melts. For example, Lü and Wang 33,34 reported that the transition of the primary phase crystallization to the non-equilibrium peritectic phase crystallization is dependent on the degree of undercooling of the melt. In the present study, the undercooling of the MoSiBTiC alloy melt reached 100–130 °C as shown in Figs 5 and 6.…”
Section: Discussionmentioning
confidence: 99%
“…Deep undercooling may affect the solidification pathway of alloy melts. For example, Lü and Wang 33,34 reported that the transition of the primary phase crystallization to the non-equilibrium peritectic phase crystallization is dependent on the degree of undercooling of the melt. In the present study, the undercooling of the MoSiBTiC alloy melt reached 100–130 °C as shown in Figs 5 and 6.…”
Section: Discussionmentioning
confidence: 99%
“…speed camera to visualize and investigate the growth mechanism process of Si and Ge. Lü et al 19 used high speed camera to examine the transition of Ni-Zr alloy to its peritectic phase under different undercooling in an electromagnetic levitation system. Fukuyama et al 20 developed an ultrahigh-temperature thermal analyser, which was used in-conjunction with electromagnetic levitation to perform solidication and microstructural study of MoSiBTiC alloy.…”
mentioning
confidence: 99%
“…This technology is widely applied to the researches about the undercooling materials [3,4], the metastable materials [4,5] and other new functional materials [6][7][8] by avoiding the contact between the test sample and the container, and it could effectively restrain the heterogeneous nucleation. Compared to other suspension methods such as the electromagnetic suspension system [9,10], the aerodynamic suspension system [11] and the acoustic suspension system [12], the electrostatic suspension system could suspend the nonmetallic materials, realize the suspension in vacuum environment and separate the heating from the suspension. More importantly, the electrostatic suspension system causes little influence on the test sample with better control performance [13].…”
Section: Introductionmentioning
confidence: 99%